Isoenzyme genotyping and phylogenetic analysis of oxacillin-resistance Staphylococcus aureus isolates - Marcelo Fabiano Gomes Boriollo; Manoel Francisco Rodrigues Netto; Jeferson Júnior da Silva; Thaísla Andrielle da Silva; Maysa Eduarda de Castro; Júlio César Elias; José Francisco Höfling (Universidade Estadual de Campinas, 2017)
Aim: The propagation of S. aureus in hospital and dental environments is considered an important public health problem since resistant strains can cause serious infections in humans. The genetic variability of 99 oxacillin-resistant S. aureus isolates (ORSA) from the dental patients (oral cavity) and environments (air) was studied by isoenzyme genotyping. Methods: S. aureus isolates were studied using isoenzyme markers (alcohol dehydrogenase, sorbitol dehydrogenase, mannitol-1-phosphate dehydrogenase, malate dehydrogenase, glucose dehydrogenase, D-galactose dehydrogenase, glucose-6-phosphate dehydrogenase, catalase and /-esterase) and genetic (Nei's statistics) and cluster analysis (UPGMA algorithm). Results: A highly frequent polyclonal pattern was observed in this population of ORSA isolates, suggesting various sources of contamination or microbial dispersion. Genetic relationship analysis showed a high degree of polymorphism between the strains, and it revealed three taxa (A, B and C) distantly genetically related (0.653dij1.432) and fifteen clusters (I to XV) moderately related (0.282dij0.653). These clusters harbored two or more highly related strains (0dij0.282), and the existence of microevolutionary processes in the population of ORSA. Conclusion: This research reinforces the hypothesis of the existence of several sources of contamination and/or dispersal of ORSA of clinical and epidemiologically importance, which could be associated with carriers (patients) and dental environmental (air).